A Compact Optical MEMS Pressure Sensor Based on Fabry–Pérot Interference - Qi, Yonghong; Zhao, Minghui; Li, Bo; Ren, Ziming; Li, Bing; Wei, Xueyong (Sensors (Basel, Switzerland), 2022)
Pressure sensors have important prospects in wind pressure monitoring of transmission line towers. Optical pressure sensors are more suitable for transmission line towers due to its anti-electromagnetic interference. However, the fiber pressure sensor is not a suitable choice due to expensive and bulky. In this paper, a compact optical Fabry–Pérot (FP) pressure sensor for wind pressure measurement was developed by MEMS technology. The pressure sensor consists of a MEMS sensing chip, a vertical-cavity surface-emitting laser (Vcsel), and a photodiode (PD). The sensing chip is combined with an FP cavity and a pressure sensing diaphragm which adopts the square film and is fabricated by Silicon on Insulator (SOI) wafer. To calibrate the pressure sensor, the experimental platform which consists of a digital pressure gauge, a pressure loading machine, a digital multimeter, and a laser driver was set up. The experimental results show that the sensitivity of the diaphragm is 117.5 nm/kPa. The measurement range and sensitivity of the pressure sensor are 0–700 Pa and 115 nA/kPa, respectively. The nonlinearity, repeatability, and hysteresis of the pressure sensor are 1.48%FS, 2.23%FS, and 1.59%FS, respectively, which lead to the pressure accuracy of 3.12%FS.